Status Limnologis Danau Siombak, Medan, Sumatra Utara - Ahmad Muhtadi; Yunafsi; Rusdi Leidonald; Sarah D. Sandy; Adil Junaidy; Achmad T.Daulay (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Limnological Status of Lake Siombak, Medan, North Sumatra. Lake Siombak is located in the coastal area of Medan city, making its waters influenced by the tides. The lake serves as a water catchment, flood control, fishing area, and tourist destination. Various activities in the lake have led to changes in the environmental quality of the lake. To maintain the sustainability of the lake, efforts are needed for proper management. Lake management should begin with a good understanding of the nature and characteristics of the waters. This study aimed to determine the limnological status of Lake Siombak through morphometric analysis, aspects of physics, chemistry, and biology, as well as trophic status of the waters. Morphometry included dimensions of water surface and subsurface. Physics parameters included temperature, Total Suspended Solid (TSS), water clarity, electrical conductivity (EC), and salinity. Chemical parameters included pH, dissolved oxygen (DO), Biological Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), nitrates, and phosphates. Biological parameters included community structure of nekton and benthos. Measurement of lake morphometry was performed in April 2014 at high and low tides. Measurements of water quality and biological sample collection were conducted in May-July 2014 at high and low tides. The results showed that Lake Siombak has an area of 41.44 ha with a maximum depth of 5 m at high tide and 4 m at low tide. Based on the aspects of physics, chemistry, and biology of the waters, Lake Siombak was categorized as an open waters influenced by the tides and was saline with high level of oxygen. The lake water retention time (Rt) was 15.65 hours and discharged (Q) 3.7 x 107 m3/h of water at high tide and 3.0 x 107 m3/h at low tide. High phosphate concentration indicated these waters have already been polluted. However, the water quality of Lake Siombak was still suitable for fishing activities. Benthos and nekton communities were relatively unstable. Benthic community was dominated by Blue Mussel (Mytilus edulis) at high tide (57%) and Red-rimmed Melania (Melanoides tuberculata) at low tide (41.34%). Nekton community was dominated by Blue Panchax (Aplocheilus panchax) at high tide (74.07%) and low tide (64.79%). In general, Lake Siombak was classified as eutrophic.